A profitability analysis of product sales and leasing in supply chains - Demirayak, Caner. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2010., 2010)
As a result of marketing policies based on cheaper and less durable products with short life cycles, the consumption and disposal rates have increased and therefore many developed countries introduce laws and regulations to minimize the disposal of end-of-life products. Thus, collecting used products, recycling and remanufacturing have become important and profitable operations for many companies. Since components are used without losing their added values for the majority of the multi-component durable products, remanufacturing is a better alternative than recycling. However, product remanufacturing has uncertainties in quality, quantity and timing of returns since the manufacturing systems are generally based on the sales of products, not the sales of services. Our aim in this study is to compare the profitability of systems based on sales of products with or without remanufacturing and examine whether or not the sales of services is more advantageous than sales of goods. For this purpose, three different structures are constructed. The first structure (TSM) is a traditional supply chain where products are sold to customers while the second structure (SRM) includes reverse supply chain where used products are acquired by the manufacturer for remanufacturing and both remanufactured and new products are sold. Finally, the third structure (LM) considers a closed loop supply chain where products are leased and leased products are remanufactured at the end of each lease period. To compare the profitability of supply chains with respect to product life cycle, these supply chains are modeled as queuing networks with GI/G/1 and GI/G/∞ stations. Then, these networks are analyzed using parametric decomposition method in order to obtain performance measures. After validating the accuracy of the queuing network models using simulation, profit functions for each model are defined using the performance measures. Then, the profitability of the structures is compared while changing the values of parameters of interest. Also, cannibalization effect of the remanufactured products and effects of proper design are examined. Finally, conclusions are derived.
Keywords: Marketing -- Management -- Econometric models.; Telemarketing.; Strategic planning.